Modelo explicativo para intenção de uso de fintechs : um estudo sobre a perspectiva dos consumidores brasileiros das gerações Y e Z - Almeida, Caio Bernardo Santos (2020)
The term fintech, although it has been known for some time abroad, is still considered recent in the Brazilian context, consisting of startups in the financial area. This research aimed to verify the influence of individual attributes related to innovation and perceptual variables on the intention to use fintechs by Brazilian consumers of generations Y and Z, users and nonusers of this platform. The intention to investigate these categories of consumers is justified by the need to have a perspective of those who already use these financial agents, but also to understand the factors responsible for the intention or not of use, through the theoretical model developed by the author and empirically tested, which sought to explain the intention to use fintechs based on variables related to innovative characteristics (Innate Innovativeness and Domain of Specific Innovation) and consumer perceptions (Utility, Ease of use), including the influence of security risk got that. It is a correlational study, with descriptive and explanatory purposes, of a quantitative nature through an online survey with users and non-users of fintech services, totaling 297 individuals from generations Y and Z. The instrument of Chauhan, Yadav and Choudhary (2019), originally used in research in India, was adapted with the addition of some items. Before applying the research instrument to the sample, procedures were carried out to verify the theoretical adequacy of the instrument to the Brazilian context (back translation, semantic analysis and analysis of judges), for the adequacy and validation of the instrument in the study population. The data obtained went through exploratory and adjustment procedures through the software IBM SPSS Statistics v.20, in addition to the analysis of the basic assumptions to verify the adequacy to the general parametric model (TABACHNICK; FIDELL, 2007). The theoretical model developed during the research, inspired by the model of Chauhan, Yadav and Choudhary (2019), was tested using the Path Analysis technique in the AMOS v.22 software. The final model presented an explanatory power of 62% of the intention to use fintechs, after undergoing adjustments such as the exclusion of the innate innovativeness variable and the introduction of covariance between the Perceived Utility and Perceived Ease of Use variables. It was concluded that the Domain of Specific Innovation considerably influences the perception of utility and ease of use of fintechs (β = 0.51, for both). In turn, these two perception indicators are the ones that most influence the intention to use fintechs, with the explanatory contribution of Perceived Utility prevailing (β = 0.35). Although the Perceived Security Risk hardly affects the intention to use this innovation tool (β = -0.06), it showed an inverse relationship, as predicted by the theoretical model of this research.